An efficient method for fractionated whole rodent brain radiation. (1st May 2013) - Semmler, Alexander; Garbe, Stephan; Moskau, Susanna; Frisch, Christian; Eter, Nicole; Schlegel, Uwe; Linnebank, Michael
<x xml:space="preserve">Abstract</x> Objective: In order to test for mechanisms of whole brain radio therapy side effects and possible neuroprotective measures, a rodent model is desirable. In many models, a high single dose of 8-20 Gray (Gy) of whole brain irradiation is used. These experimental radiation protocols do not closely reflect the clinical situation, where the cumulative dosage is applied in smaller fractions. We describe an efficient method to perform repetitive, fractionated whole brain radio therapy to the rat brain. Methods: Fifteen-week-old rats were irradiated with a dose of 5 or 10 Gy on four consecutive days, resulting in a cumulative dose in opposing fields of 20 Gy (n = 15) and 40 Gy (n = 17), respectively. Sham-irradiated rats (n = 14) received the same procedure but without application of cranial irradiation. Four collimators with a diameter of 3 cm each were used to place four rats and an ionization chamber simultaneously in the dose field for monitoring. Results: Fourteen days after the procedure, irradiated animals showed decreased open-field activity (two-tailed t-test, sham versus 20 Gy, P<0·001; sham versus 40 Gy, P = 0·002), but no cognitive deficit as indicated by latencies in the Morris water maze test. Six weeks after the irradiation, no group showed alterations of histopathology such as vascular changes, demyelination, or white matter necrosis. Discussion: The proposed model represents an efficient and safe method to perform fractioned high-dose irradiation of the rodent brain. Speculatively, it is possible to increase the cumulative dosage and dose per fraction used in this model to achieve a higher degree of radiation-induced toxicity.